We need better mental health court data - Fradella, Henry F. (Criminal justice studies, 2024)
Although numerous studies evaluate the efficacy of mental health courts (MHCs), most of this research examines a limited number of variables, often focusing on graduation and recidivism rates for a single court or county. By contrast, there is little systematic research that evaluates MHCs comprehensively. This article examines why that might be the case by comparing and contrasting publicly available reports on MHCs from across the United States. Notably, more than half of all states have no such reports available on the websites of their judicial branches, state departments of health and human services, or similar state agencies. Of the 23 U.S. jurisdictions that make an evaluation report publicly accessible, many are more than a decade old and most fail to report a host of relevant data that researchers would need to conduct analyses on MHC effectiveness. The article offers some suggestions for addressing this problem.